1989
DOI: 10.1111/j.2044-8260.1989.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy vs. self‐management training in the treatment of chronic headaches

Abstract: In view of the association between chronic headaches and depression, this study compared a cognitive therapy package designed for depression with a relatively standard behavioural treatment package designed for headaches (self-management training), in terms of their effects on headaches and depressive symptoms. Fifty-five subjects suffering from chronic headaches (tension, migraine and combined) were randomly assigned to the two treatment conditions. Cognitive therapy and self-management training were equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
0
19
1
2
Order By: Relevance
“…24,25 The study by Martin et al 24 reported data at several time points, with 12-month follow-up data reported here. Richardson and McGrath 25 had an additional waiting list control arm (reported above).…”
Section: Cbt Versus Cbt Self-managementmentioning
confidence: 52%
See 1 more Smart Citation
“…24,25 The study by Martin et al 24 reported data at several time points, with 12-month follow-up data reported here. Richardson and McGrath 25 had an additional waiting list control arm (reported above).…”
Section: Cbt Versus Cbt Self-managementmentioning
confidence: 52%
“…Basler et al 23 Blanchard et al 16 Blanchard et al 20 Holroyd et al 17 Holroyd et al 21 Martin et al 24 Martin et al 26 Mosley et al 18 Richardson and McGrath. 25 Tobin et al 19 Random sequence generation?…”
Section: Authors Biasmentioning
confidence: 99%
“…Thus, at the most general level, psychological factors are recognised as having an association with physical morbidity among both adults and adolescents (Zealley, 1983;Cadman, Boyle, Szatmari & Offord, 1986;Mechanic & Hansell, 1987;Weinman, 1987;Lewinsohn, Seeley, Hibbard, Rohde & Sack, 1996;Cohen, Pine, Must, Kasen & Brook, 1998), while muscular tension is associated with pain (Weisenberg, 1977), headache (Martin, Nathan, Milech & van Keppel, 1989) and hyperventilation (Garsen & Rijken, 1986). This would suggest that one possible reason for the relative increase in certain health measures, such as headaches, dizziness and 'poor' self-rated health, among females, is that they are associated with psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic headaches, few studies have been performed since the report by Martin et al [112] in 1998 showing that a CBT designed to treat depression is more effective in patients with high chronicity while self-management has a better outcome when depression is low. In high-frequency migraine (mean 5.5 migraine days/month), addition of behavioural management alone to optimized acute treatment had no significant effect, whereas the combination of behavioural therapy with a beta blocker significantly improved outcome at 16 months [113].…”
Section: Cognitive-behavioural Therapymentioning
confidence: 99%